Stargardt's Disease : Case Report - Dian Ariani; AK Ansyori; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2018)
Introduction. The Stargardt disease is a frequent macular dystrophy and the most common cause of decreased central visus in adults below 50 years. This condition is caused by the presence of mutations in the ABCA4 gene, located in the chromosome chain 1 short sleeve, which encode the ATP-binding cassette (ABC) protein transporter expressed by the outer trunk cell segment. Case Presentation. A man, 59 years old, civil servants, was living in the city, came to the eye Polyclinic RSMH on February 4, 2016. From anamnesis, main complaint of the right eye was view blurred since 2 years ago. The history of the illness since ± 2 years ago, the sufferer complained the right eye view blurred slowly, the longer the more blurred. Often glare (+), the sufferer also complains to see black spots, such as enclosed curtains (-). Conclusion. A case of Stargardt disease has been reported in a 58-year-old male. Patients come with complaints of blurry vision slowly in both eyes. On posterior segment examination, a picture of atrophy in the macula that typically leads to Stargardt disease. Additional examination of OCT also showed a stretch of RPE depletion. Supportive therapy such as correction with low vision aids or the provision of sun protective glasses can help in the daily lives of patients.